Business ethics and the bandwagon effect: An analysis of downsizing in the South African industrial situation - David A.L. Coldwell (South African Journal of Business Management, 1993)
Downsizing has become a widely used managerial instrument for ensuring the continued profitability of organizations in adverse business/economic situations, both within South Africa and overseas. However, the ethical and business/economic implications of downsizing have not been extensively researched in the South African context. The aim of this article is to expose and analyze the ethical and managerial Issues that underlie the downsizing process. It is suggested in this article that a macro, strategic solution to the downsizing problem is required and that piecemeal tinkering is ineffective. It is maintained that downsizing in the current South African industrial situation is neither ethical nor managerially prudent.
Keywords: 650